The effects of different root canal irrigation protocols and artificial aging procedures on the bond strength between dentin and hybrid ceramic posts - Celalettin Topbaş; Şevki Çınar; Bike Altan; Dursun Ali Şirin; Mehmet Ali Fildişi (BMC, 2022)
Abstract The purpose of this study is to investigate the effects of different root canal irrigation protocols applied to the dentin and artificial aging procedures on the micro pushout bond strength (mPBS) between dentin and hybrid ceramic posts. Seventy-five single-rooted mandibular premolar teeth were divided into 5 groups (Gr1-5). 50 of the teeth were used for the mPBS tests (n = 10), whereas 25 were used for the smear layer examinations (n = 5). Post space were prepared and irrigated with different irrigation-protocols in each group. (Gr1:[SS], Gr2:[NaOCl] + SS, Gr3:[EDTA] + NaOCl + SS, Gr4:[MA] + NaOCl + SS, Gr5:[Ch] + NaOCl + SS). Post and core pattern were fabricated with pattern resin and a fiber post, after scanning, the posts were milled with Vita Enamic resin ceramic block, and cemented. After 7 days the roots were sliced at thicknesses of 1 mm; half of them were subjected to mPBS test, while the other half were tested after undergoing mechanical cycling for artificial aging. For data analysis, the Shapiro-Wilk test was utilized to test normal distributions, 3-way analysis of variance was used to compare mPBS, and Tukey's HSD test was conducted for multiple comparisons. SEM analysis was performed for examination of failure modes and smear layer removal. Different root canal irrigation protocols affected mPBS significantly. While Gr4 had the highest mPBS, Gr1 had the lowest. Regarding to different zones, the highest mPBS was in coronal zone, and the lowest one was in the apical zone. The aging procedure also led to a statistically-significant decrease in mPBS. Most frequent failure modes were cohesive failure in dentin and mixed failure. Irrigation with 7%MA (Gr4) showed better performance than 17% EDTA (Gr3) in smear layer removal, especially at the apical zone of the tooth. This is critical for the success of root canal treatment and increased the mPBS to a higher extent in all zones of the tooth.